Study on the Prevalence of Intestinal Parasites Among Children Attending Al-Daura Health Centre-Baghdad - A.S., Basima (Iraqi National Journal of Nursing Specialties, 2005)
Abstract The present study on the prevalence of intestinal parasitic infection from July 2003 to July 2004 ,was conducted among children aged(less than 5 -14 )years attending AL-Daura Health Centre in Baghdad City .(350) specimen were choosen randomly and examined, 160(45.7%) of these were infected , 140 (87.5%) harboured one parasite while 20 (12.5%) harboured more than one parasite.190 (54.3%) were non infected with any of intestinal parasite . It was observed that the most common intestinal protozoa among children is Giardia lamblia, followed by Entamoeba histolytica and Blastocystis hominis with prevalence rate of infection (30.75%) for the last two parasites . Non pathogenic protozoa (E. coli ,I .butschlii,C. mesenili and E.nana)were found with a prevalence rate of (6.25%, 3.12% ,1.87%,1.87%) respectively . This stuy revealed that the prevalence rate of helmenth infection (18.75%)was lower than the protozoa (68.71%) . It was found that children in the age group ( less than 5 ) years are more susceptible to the infection with G. lamblia (17.5%) and B. hominis (9.37%) , while the infection with E. histolytica was within the age group (5 -14) years. Prevalence of infection with helminths increases with age .